Metamorphopsia and Morphological Changes in the Macula after Scleral Buckling Surgery for Macula-Off Rhegmatogenous Retinal Detachment. (25th June 2021) - Xu, Sisi; Wang, Ling; Kong, Kangjie; Li, Gang; Ni, Yingqin
Abstract : Purpose . To observe the changes in metamorphopsia after scleral buckling (SB) surgery for macula-off rhegmatogenous retinal detachment (RRD) and its association with morphological changes in the macula. Methods . This prospective study included 20 eyes of 20 patients. Before surgery and 1, 3, 6, and 12 months after surgery, metamorphopsia measured by M -charts and best-corrected visual acuity (BCVA) and macular microstructures assessed using optical coherence tomography were recorded. Results . Both the vertical and horizontal M -scores improved significantly after SB surgery. BCVA also improved gradually. The mean M -score in the eyes with a continuous external limiting membrane (ELM) was smaller than that in the eyes with a disrupted ELM (P = 0.008 ). Preoperative and postoperative BCVA did not correlate with the mean M -score at any time point. The other studied parameters, namely, the duration of RRD, the height of retinal detachment, central foveal thickness, inner nuclear layer thickness, and continuation of the ellipsoid zone, were also not relevant. Conclusions . The continuation of the ELM may be a critical factor in determining the severity of metamorphopsia after SB surgery for macula-off RRD.